BIG DATA IMPLEMENTATION IN SMALL AND MEDIUM ENTERPRISES IN INDIA AND POLAND - Zdzislaw POLKOWSKI; Rajesh KHAJURIA; Sameer ROHADIA (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
Today we are having a huge information explosion across the world. Earlier the amount of information was increasing arithmetically, but today, information has expanded in geometric series. The concept of big data has been around for years; most organizations now understand that if they capture all the data that streams into their businesses, they can apply analytics and get significant value from it. Big Data isn’t just for large enterprises with large budget. Today, small companies can have the benefits of the monumental amounts of digital data to make right and fast decisions to develop their enterprises. In fact, over the last couple of years, small and mid-size companies have seen more big date deployments than the big competitors. In India and Poland, the data boom isn’t just limited to big enterprises, the growth of big data startup/ technology vendors, is helping SMEs in scaling up infrastructure capabilities and driving insights from data. The increased availability of accessible, cheap data centres delivered by cloud vendors, has brought down the costs of upfront investment for small businesses, thereby reducing the market entry barrier. It is the question of choosing the right analytics vendors that fits the bill for small businesses. This paper aimed at designing a framework of Big Data implementation in SMEs. The reason for selecting these two countries is that there are international tie-ups between two universities of both countries.